PWE-212 Genotype-phenotype correlations in cystic fibrosis patients with pancreatitis highlights an increased likelihood of pancreatic insufficiency and identifies unique mutation pairs that potentially predispose to and protect from pancreatitis. (22nd June 2015) - Westaby, J; Butt, MA; Shahid, S; Sangwaiya, A; Burgess, J; Gooding, I; Steel, A; Wadsworth, C; Vlavianos, P; Simmonds, N; Westaby, D
Abstract : Introduction: 1–2% of cystic fibrosis (CF) patients develop symptomatic pancreatitis. Studies have shown these patients present later in life, are pancreatic sufficient (PS) and have a less severe CF phenotype. This study aimed to evaluate the genotype:phenotype relationship of CF patients with pancreatitis in a tertiary referral centre for CF. Method: CF patients with a history of pancreatitis were identified from 1216 patients in The Royal Brompton Hospital CF database. Each case was age and sex matched with controls. Clinical information on age, sex, PS status, age when CF diagnosed, CF genotype and mortality were collected. To compare pancreatitis patients with controls, a two tailed t-test (age of CF diagnosis, R117H mutation rate) and Kaplan-Meir survival curves (rate of PI and mortality rates) were utilised. Results: 37 patients (51% females) with pancreatitis were matched to 135 controls (3:1/4:1). Mean age of CF diagnosis was significantly higher in the pancreatitis group (19yrs) than controls (10.6yrs; p = 0.046). Median time between CF diagnosis and pancreatitis was 17 yrs (range 8–36 yrs). 65% (n = 24) of pancreatitis sufferers were PS at presentation to adult services; of these 63% (n = 15) remained PS until their most recent review or death. Furthermore, 67% (n = 16) suffered with recurrent or chronic pancreatitis. Using Log-rank (Mantal-Cox), there was no difference in survival between pancreatitis patients and controls (p = 0.97). However, pancreatitis patients were significantly more likely to develop PI (p = 0.012). The ^F508:R117H mutation pair was noted more frequently in pancreatitis patients (18.9%;n = 7) than controls (3.8%;n = 5) but not significancantly so (p = 0.56). Interestingly in 43% (n = 16) of the remaining pancreatitis patients, 15 mutation pairs unique to this group were identified. Similarly in controls, 50% (n = 65) had mutation pairs unique to this group. Conclusion: CF patients who suffer with pancreatitis are significantly more likely to develop PI than those who do not. They present with CF at an older age but this does not affect their survival. The R117H mutation is seen more frequently in the pancreatitis group but not significantly so for this phenotype. We have identified a number of mutation pairs that seem to either predispose or protect CF patients from pancreatitis. Disclosure of interest: None Declared.